FINANCIAL IMPACT OF BRAND STRATEGY: AN ANALYSIS OF KEY FINDINGS AND FUTURE RESEARCH PROSPECTS - Novianha Pynatih, Ngurah Made; Dwika Ayu Amrita, Nyoman; Aripin, Zaenal (Yayasan Kreatif Indonesia Emas, 2024)
In an increasingly competitive business world, brand strategy has become a key factor in determining the success and financial performance of a company. In this research, we investigate the financial impact of a strong brand strategy on a company's financial performance, as well as the external environmental factors that influence this relationship. Through in-depth analysis, we found that a strong brand can make a significant contribution to a company's revenue, profit margins and valuation. However, companies also need to consider the costs and risks associated with building and maintaining a strong brand. Additionally, changes in the external environment, including changes in regulations and consumer behavior, as well as the influence of technology, integration with other strategies, and the role of leadership and corporate culture, can influence the financial impact of a company's branding strategy. Therefore, further research in this regard is needed to deepen understanding of the complexity of the relationship between brands and financial performance, as well as provide guidance for business practitioners in optimizing their brand strategies to achieve competitive advantage and long-term success.